The feeding preference and bite response between Microtus fortis and Broussonetia papyrifera - Wang, Shuangye; Chen, Zihao; Wang, Mengxin; Zhang, Meiwen; Zhang, Chen; Huang, Tian; Zhao, Yunlin; Xu, Zhenggang (Frontiers in Plant Science, 2024)
Introduction: Broussonetia papyrifera is a dioecious plant that is rich in various metabolites and widely distribute in Asia. Microtus fortis is a rodent that often causes damage to crops, especially in the Dongting Lake region of China. There is a wide overlap in the distribution areas for the above species and the M. fortis feeds on the leaves of the B. papyrifera. Preliminary experiments have shown that the reproduction of M. fortis is inhibited after feeding on the leaves of the B. papyrifera.In order to explore the potential of using B. papyrifera to develop botanical pesticides, we investigated the palatability and reactive substances. The feeding frequency of M. fortis on B. papyrifera leaves to that of on daily fodder and Carex brevicuspis that is the primary food for the wild population were compared. We also attempted to identify the responsive substances in B. papyrifera leaves that were bitten by M. fortis using metabolome analysis.In general, B. papyrifera leaves exhibited a stronger attraction to M. fortis. M. fortis foraged B. papyrifera leaves more frequently, and the intake was higher than that of the other two. Differential metabolites were screened by comparing normal leaves and leaves bitten by M. fortis, meanwhile with the intervention of clipped leaves. A total of 269 substances were screened, and many of these were involved in the biosynthesis of secondary metabolites, including terpenoids and alkaloids. These substances may be related to the defence mechanism of B. papyrifera against herbivores.Discussion: These findings support further research examining animal--plant interactions and simultaneously provide insights into the utilisation of B. papyrifera resources and the management of rodents. The good palatability and the defence of B. papyrifera leaves suggest that they have the potential to contribute in development of plant rodenticide.